Ethnotaxonomical considerations and usage of ichthyofauna in a fishing community in Ceará State, Northeast Brazil - Pinto, Márcia Freire (BioMed Central, 2013)
BACKGROUND: Artisanal fishery is one of the most important economic activities for human populations living in coastal areas. The traditional knowledge that fishermen have of fishes is of utmost importance for the establishment of conservation strategies for many species. This study aimed to analyse the knowledge of and utilization of fishes by the artisanal fishermen in a fishing community on the coast of Ceará State (Northeast Brazil). METHODS: In 2011, a number of semi-structured interviews were performed with fishermen with more than 20 years of fishery experience. The interviews were about fisheries (collecting spots, artefacts, etc.) and fish use. The fishes cited by the fishermen were identified scientifically and ethnotaxonomically. RESULTS: Considered masters of fishery, they cited 162 vernacular names of fishes, which corresponded to 290 different species, also including other animals such as dolphins, porpoises, whales and manatees. The criteria for the classification of the fishes were well known and utilised by the fishermen, and they were based on morphology, behaviour, habitat and the importance of commercial and fishing activities. Four hierarchical categories were identified in their classification system: kingdom, life-form, generic and specific. The fish nomenclature created by the fishermen was mostly composed of generic and monotypic names. The main uses of fish were for food and commercial purposes. CONCLUSIONS: The results stress the richness and complexity of the knowledge of the artisanal fishermen of Redonda Beach, and they provide support for the possibility of future studies and for the development of management plans and the management of wildlife resources.